Impact of high-frequency harmonics (0–9 kHz) generated by grid-connected inverters on distribution transformers. (November 2020) - Yaghoobi, Jalil; Alduraibi, Abdulrahman; Martin, Daniel; Zare, Firuz; Eghbal, Daniel; Memisevic, Rizah
Highlights: Impact of current harmonics on distribution transformer K-factor is investigated. Simulation and practical results have evaluated this factor in different conditions. Current harmonics higher than 2 kHz from PV inverter highly contribute in Kf value. Field measurements show that high-frequency harmonics can increase eddy losses by 33%. The loss due to higher frequency harmonics causes 22% acceleration in ageing. Abstract: The level of current harmonics circulating in a transformer winding can affect its operating temperature and lifetime. Although the existing standards mainly consider the impact of harmonics up to 2 kHz, higher frequency harmonics generated by high power converters utilized in renewable energy sources can also contribute to the temperature rise of a transformer. Pulse Width Modulated (PWM) voltage generated by power converters can generate significant high-frequency harmonics at its switching frequency. The switching frequency of converters in high-power applications is mainly between 2 and 9 kHz. Consequently, in this article, the importance of also using higher frequency harmonics in calculating transformer core loss and temperature rise is investigated as per IEEE standard conclusions. For that purpose, transformer K-factor values have been calculated in simulated and practical distribution systems, in both long-term and transient conditions. The results confirm the importance of considering higher-order current harmonics (more than 2 kHz) when calculating K-factor and estimating transformer temperature rise and lifetime.